2004
DOI: 10.1111/j.1525-1594.2004.07298.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Expanded Polytetrafluoroethylene (ePTFE Gore‐Tex) Surgical Membrane for Coronary Artery Grafting: Does ePTFE Surgical Membrane Predispose to Postoperative Mediastinitis?

Abstract: The advantage of completely closing the pericardium after a coronary artery bypass grafting is the avoidance of injury of the heart and grafts during a re-operation. However, it would obviously be counterproductive to close the pericardium with a substitute that is predisposed to infection. This study was designed to evaluate the safety of ePTFE surgical membrane in comparison to native pericardium or autologous tissue. Between January 1992 to March 2003, 695 coronary artery bypass graftings were performed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…The gelatin was isolated by an alkaline process from bovine bone with an isoelectric point of 5.0 as previously described (10). The water content of gelatin hydrogel was prepared to 94% by chemical cross-linking at 140°C for 72 h. The gelatin was reinforced by polytetrafluoroethylene (W. L. Gore and Associates, Inc., Flagstaff, Arizona) pericardial sheet (12) to provide strength against the beating heart. Human recombinant bFGF (Kaken Pharmaceutical Co., Tokyo, Japan) was incorporated into the gelatin hydrogel by impregnation for 3 h before implantation.…”
Section: Methodsmentioning
confidence: 99%
“…The gelatin was isolated by an alkaline process from bovine bone with an isoelectric point of 5.0 as previously described (10). The water content of gelatin hydrogel was prepared to 94% by chemical cross-linking at 140°C for 72 h. The gelatin was reinforced by polytetrafluoroethylene (W. L. Gore and Associates, Inc., Flagstaff, Arizona) pericardial sheet (12) to provide strength against the beating heart. Human recombinant bFGF (Kaken Pharmaceutical Co., Tokyo, Japan) was incorporated into the gelatin hydrogel by impregnation for 3 h before implantation.…”
Section: Methodsmentioning
confidence: 99%
“…To channel or restrict the flow of liquids requires non‐permeable materials; to transport gases requires porous media. Porous, water‐repellent materials based on expanded polytetrafluoroethylene (ePTFE, Gore‐Tex, Nafion, Teflon) and other polymers have been useful in a wide range of applications, from high performance fabrics and membrane filters to fuel cells, surgical implants, and lung‐assist devices . The relatively high cost (from ∼USD$1500 m ‐2 for Nafion to ∼$29 m ‐2 for Gore‐Tex) of these materials has, however, limited their utilization for applications requiring a low‐cost or single‐use format.…”
Section: Introductionmentioning
confidence: 99%
“…Permanent presence in the mediastinum of non-resorbable foreign material additionally poses questions with regard to its implications in terms of infection. However, over the past two decades, different studies concluded that ePTFE membrane can safely be used in cardiac surgery to limit adhesions without increasing the risk of infection [ 27 – 30 ].…”
Section: Discussionmentioning
confidence: 99%